Taxonomic and Phylogenetic Divergence of Aspergillus salvadorensis (UES 001 strain) Isolated from the Morazán area of El Salvador and Its Close Relatives - Vásquez Hidalgo, Antonio (International Journal of Molecular Microbiology, 2026)
This study presents the taxonomic and genomic description of a new species of fungus, Aspergillus salvadorensis (UES 001 strain), which was isolated in the Morazán area of El Salvador. The research, related to the University of El Salvador (UES), used a polyphase taxonomy perspective that combined morphological analysis and molecular phylogeny based on the ITS marker. The findings of the phylogenetic analysis showed that this species belongs to the Nigri section and has a close evolutionary relationship with Aspergillus niger and Aspergillus neoniger, but presents enough genetic differences to be considered as an independent species. The registration of this discovery in international databases, such as Fungal Names (FN 573057), supports its scientific integrity. The massive genomic information has been deposited in the NCBI’s GenBank repository under the identifier PRJNA1365736, establishing the UES 001 strain as the type strain for future research. This work not only contributes to the knowledge of neotropical mycological biodiversity but also provides a fundamental genetic resource for the development of biotechnological applications in the production of industrial enzymes.